Penerapan Strategi Digital Marketing pada UMKM Roti Bakar Family Cabang Puseur Jaya Karawang - Krisna Agung; Citra Savitri; Syifa Pramudita Faddila (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The increasing development of MSMEs in Karawang Regency is a challenge in business competition. Roti Bakar Family, founded in 2016, was faced with the need to formulate an effective marketing strategy. This research uses quantitative descriptive methods with a focus on the implementation of digital marketing in the UMKM Roti Bakar Family Branch in Puseur Jaya Village, Karawang, using questionnaires, interviews and observations. This research uses SWOT analysis with primary and secondary data to identify business strengths, weaknesses, opportunities and threats. The analysis results show that Roti Bakar Family is in Quadrant I, supporting an aggressive strategy with environmental opportunities and external forces. Companies can leverage social media, online promotions, and technological innovations to increase customer visibility and engagement. Therefore, an effective digital marketing strategy will be the key to strengthening Roti Bakar Family's position in the competitive Karawang Regency MSME market.